2014
DOI: 10.1021/es5026933
|View full text |Cite
|
Sign up to set email alerts
|

Silicon is a Frequent Component of Atmospheric Nanoparticles

Abstract: Nanoparticles are the largest fraction of aerosol loading by number. Knowledge of the chemical components present in nanoparticulate matter is needed to understand nanoparticle health and climatic impacts. In this work, we present field measurements using the Nano Aerosol Mass Spectrometer (NAMS), which provides quantitative elemental composition of nanoparticles around 20 nm diameter. NAMS measurements indicate that the element silicon (Si) is a frequent component of nanoparticles. Nanoparticulate Si is most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 64 publications
9
50
0
Order By: Relevance
“…Another interesting observation was that PM2.5 mass often increased when using/applying personal care products such as skin creams, hair remedies, and antiperspirants. This observation is consistent with the reports of Bzdek et al (2014) and Tang et al (2015) and who found siloxanes present in personal care products are very common components of urban particles. The exact origin of PM spikes observed during restroom visits is unknown; however, a variety of production mechanisms can be envisioned.…”
Section: Personal Monitoringsupporting
confidence: 93%
“…Another interesting observation was that PM2.5 mass often increased when using/applying personal care products such as skin creams, hair remedies, and antiperspirants. This observation is consistent with the reports of Bzdek et al (2014) and Tang et al (2015) and who found siloxanes present in personal care products are very common components of urban particles. The exact origin of PM spikes observed during restroom visits is unknown; however, a variety of production mechanisms can be envisioned.…”
Section: Personal Monitoringsupporting
confidence: 93%
“…The EDS elemental analysis of particles collected during the three types of activities showed a chemical composition similar to that generated by other anthropogenic and natural sources [21,42]. …”
Section: Discussionmentioning
confidence: 99%
“…The probability that a newly formed nanoparticle will grow to a CCN-relevant size depends on its growth rate relative to the loss rate from, e.g., coagulation or scavenging by preexisting aerosols (Kuang et al, 2010). Uncertainties in predicting the conditions that favor CCN formation make it challenging to accurately predict future impacts of radiative forcing (Carslaw et al, 2013).…”
Section: Introductionmentioning
confidence: 99%